An Analysis of Nature of Car Ownership Among Pondicherrians - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
This descriptive study, based on primary data collected by surveying 150 car owners in Puducherry, has revealed that 40% of them, mostly government employees, have more than one car in their family. Further, majority of the car owners,especially the middle aged, are aspiring to change their car.Most importantly, word of mouth seems to be the most important source from which they have come to know about their car and most of them have used borrowed funds to purchase their car.